Significance of Serum Carotenoid Levels as a Biomarker of Hyperglycemia Estimated by HbA1c Measurement among Male Workers in an Industry - KOMORI, Yoshitaka; ITO, Yoshinori; IKEYAMA, Shinji; WATANABE, Satoru; SUZUKI, Koji; HAMAMATSU, Akio (Japanese journal of MHTS, 2001)
We examined subjective symptoms, lifestyle, and serum carotenoid levels of hyperglycemia according to the glycohemoglobin A1c (HbA1c) level among 320 male factory workers and 177 male office workers of a steel factory. In this cross-sectional study, office workers with a low vegetable intake and low serum levels of carotenoids, such as α- and β-carotenes, showed a greater prevalence of hyperglycemia than did those with higher levels, whereas the same trend was not seen among the steel-factory workers. Almost all subjects showing hyperlipemia among the factory workers tended to have mental-load factors, such as sleeplessness and frequent urination at night. In conclusion, healthcare management of hyperlipemia screened by peripheral Hb1cC levels appears to be important to prevent Hb1cC levels from exceeding 5.6%. Among the office workers, high serum β-carotene levels, which reflected positive lifestyle factors such as a high intake of green-yellow vegetables, were suggested to be important. For factory workers, a low frequency of mental-load factors was found to be important.